Purification and Properties of the Thrombin-Like Principle of Agkistrodon acutus Venom and Its Comparison with Bovine Thrombin - Ouyang, Chaoho; Hong, Jau-Shyong; Teng, Che-Ming (Thrombosis and Haemostasis, 1971)
By means of DEAE-Sephadex column chromatography, Agkistrodon acutus venom was separated into 12 fractions. The thrombin-like activity was concentrated in Fr.10. This fraction was rechromatographed on Sephadex G-200. A single band was found on microzone electrophoresis at pH 7.4. A single boundary with S20, w of 3.82 S, which was almost symmetrical, was observed by ultracentrifugation. The estimated molecular weight is 33,500. The chemical analysis shows that the thrombin-like principle of the venom is a glycoprotein. The specific activity is 13 times higher than that of the crude venom. The optimal pH value of the thrombin-like principle (pH 7.5) of the venom is almost identical with that of the bovine thrombin (pH 7.2). The thrombinlike principle of the venom is not affected by heparin, while the clotting activity of the bovine thrombin is inhibited by heparin. The thrombin-like principle of the venom is much more heat stable than the bovine thrombin.No clot retraction was found with the thrombin-like principle of the venom, while the marked clot retraction occurred after plasma was coagulated with thrombin.Thrombin can activate factor XIII (Fibrin stabilizing factor), while the thrombinlike principle can not.